2017
DOI: 10.1164/rccm.201506-1182oc
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling Reveals a Role for MicroRNA-218-5p in the Pathogenesis of Chronic Obstructive Pulmonary Disease

Abstract: We highlight a role for miR-218-5p in the pathogenesis of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 41 publications
4
105
0
Order By: Relevance
“…43-56) investigate the role of miR-218-5p in the response to tobacco smoke and hypothesize a role for this miRNA in COPD pathogenesis (18). They first show that expression of miR-218-5p is decreased in the lung tissue of smokers, similar to previous studies (11,19,20).…”
supporting
confidence: 58%
“…43-56) investigate the role of miR-218-5p in the response to tobacco smoke and hypothesize a role for this miRNA in COPD pathogenesis (18). They first show that expression of miR-218-5p is decreased in the lung tissue of smokers, similar to previous studies (11,19,20).…”
supporting
confidence: 58%
“…COPD patients (10) and healthy nonsmoking (10) and smoking (5) controls were recruited, and their characteristics are shown in Table 1. Subject recruitment, viruses, cell culture and viral infection, A20 plasmid, siRNA, miR-125a and -b antagomir/mimetic treatment, cloning and mutagenesis of miR-125a and -b binding sites in MAVS 3′-UTR, reporter assays, immunoblotting, cytometric bead array, immunoprecipitation, miRNA extraction and analysis, and statistical tests were performed as previously described and/or as in Supplemental Methods (27,31,57,58). In vivo.…”
Section: Methodsmentioning
confidence: 99%
“…We also showed that primary BECs (pBECs) from COPD subjects and our established in vivo model of experimental COPD have increased inflammatory and impaired antiviral responses to IAV infections, leading to more severe infection (27)(28)(29). Furthermore, miRNAs are known to be altered in COPD (30,31). However, the molecular mechanisms underpinning the heightened inflammatory response in IAV infections and defective immune responses in COPD remain unclear.…”
Section: Introductionmentioning
confidence: 95%
“…miR135b decreased the expression of interleukin 1 receptor (IL-1R1) through its 3′ UTR and was also a target of signaling through the IL-1 pathway, suggesting this miRNA as a critical regulator of IL-1-mediated neutrophilic inflammation (Halappanavar et al, 2013). Furthermore, miR-218-5p was found to be significantly downregulated in lung tissue of smoke-exposed mice and humans (Conickx et al, 2017).…”
Section: Copdmentioning
confidence: 99%